VĂN HÓA GIAO TIẾP CỦA NGƯỜI ÊĐÊ QUA TỪ XƯNG HÔ TRONG SỬ THI Y’KHING JU - Krong, Wiyapodam Buon (Trường Đại học Đà Lạt, 2023)
In communication, the way of addressing shows the attitudes and affection of the speakers and reflects the positions, perceptions, social and cultural relationships, and language abilities of the individuals in the community. To clarify the characteristics of the Ede people’s communication culture, the article analyzes the communication characteristics of the Ede people through relationships, methods, and rituals of addressing in the Y’Khing Ju epic.